2020
DOI: 10.1016/j.jamcollsurg.2019.12.037
|View full text |Cite
|
Sign up to set email alerts
|

Living Donor Liver Transplantation for Perihilar Cholangiocarcinoma: Outcomes and Complications

Abstract: BACKGROUND: Neoadjuvant therapy and liver transplantation is an effective treatment for perihilar cholangiocarcinoma (pCCA). Living donor liver transplantation (LDLT) addresses the problem of organ shortage, but has higher risk of technical complication that can be aggravated by radiotherapy. We investigated the incidence of vascular and biliary complication in pCCA compared with non-pCCA patients and their impact on patient and graft survival. STUDY DESIGN: All consecutive LDLTs (n ¼ 247) performed between 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 18 publications
2
41
0
Order By: Relevance
“…All of these patients underwent LT for PSC, while pCCC was found incidentally posttransplant, not detected in the preoperative findings due to a small tumor size of a median of 3 cm with <5% positive lymph nodes. Similar good results were presented by Tan et al [46] in PSC patients with pCCC with an OS of 89.8, 75.9, 75.9, and 73.2%, much better than the survival of de novo pCCC patients without PSC of 75.0, 58.0, 47.5, and 35.2% at 1, 3, 5, and 10 years, respectively. This difference however vanished if residual tumor was present after LT and survival was comparable inferior in both groups (Table 2).…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…All of these patients underwent LT for PSC, while pCCC was found incidentally posttransplant, not detected in the preoperative findings due to a small tumor size of a median of 3 cm with <5% positive lymph nodes. Similar good results were presented by Tan et al [46] in PSC patients with pCCC with an OS of 89.8, 75.9, 75.9, and 73.2%, much better than the survival of de novo pCCC patients without PSC of 75.0, 58.0, 47.5, and 35.2% at 1, 3, 5, and 10 years, respectively. This difference however vanished if residual tumor was present after LT and survival was comparable inferior in both groups (Table 2).…”
Section: Resultssupporting
confidence: 88%
“…Most recent studies have shown that LT is justified for patients with unresectable very early iCCC and combined HCC/iCCC, with survival outcomes comparable to those of HCC (62) (Table 2). Best results however are clearly obtained in patients who underwent LT for PSC with incidentally found pCCC, while comparable results can be obtained in PSC patients with pCCC diagnosed before LT [45, 46](Table 2). Further, there appears no difference in outcome if patients with small iCCC and combined HCC/iCCC undergo LT [47] (Table 2).…”
Section: Discussion/conclusionmentioning
confidence: 74%
“…While waiting time is not a predictor for drop‐out, the role of living‐donor LT (LDLT) remains to be clarified and may potentially represent a route for expanding the current selection criteria. The neoadjuvant radiotherapy contributes to the technical complexity of LDLT 98 . Late hepatic artery thrombosis was found to be 18.9% and portal vein complications 37.8% in a recent experience from the Mayo clinic 98 .…”
Section: Perihilar Cholangiocarcinomamentioning
confidence: 99%
“…The neoadjuvant radiotherapy contributes to the technical complexity of LDLT 98 . Late hepatic artery thrombosis was found to be 18.9% and portal vein complications 37.8% in a recent experience from the Mayo clinic 98 . Nonetheless, these complications do not impair long‐term survival 98 .…”
Section: Perihilar Cholangiocarcinomamentioning
confidence: 99%
See 1 more Smart Citation